SHE’RIYATDA RITORIK MUNOSABAT HOSIL QILISHNING IJTIMOIY-FALSAFIY ASOSLARI - Matyakupov, S. (SCIENCE and SOCIETY, 2023)
The nature of dialogue and monologue in poetry, the influence of literary speech forms on the structure of poetry is depicted in the article. The author-text-reader relationship that creates literary communication in lyrics is analyzed on the example of certain poems.
Keywords: monologue; dialogue; aesthetic attitude; literary skill; expressive style